The American Synthetic Rubber Research Program - Morris, Peter J. T. (Chemical Sciences in Society, 2017)
This history of the government-funded synthetic rubber research program (1942-19 6) offers a rare analysis of a cooperative research program geared to the improvement of existing products and the creation of new ones. The founders of the program believed the best way to further research in the new field was through collaboration among corporations, universities, and the federal government. Morris concludes that, in fact, the effort was ultimately a failure and that vigorous competition proves the best way to stimulate innovation. Government programs, like the rubber research program, are far better at improving existing products, the author contends, than creating wholly new ones.